Analysis on the Evolution and Development of Chinese Education Based on the History of Chinese and Foreign Education - Han, Daoriao (Pacific International Journal, 2023)
This paper provides an overview of the evolution of Chinese and foreign education, examining the origins, historical developments, and current reforms in both contexts. The study explores the relationship between human history and the development of education, emphasizing the influence of geographical location, lifestyle, and thinking patterns on different educational origins. The research methods employed include literature research and comparative analysis, enabling a comprehensive understanding of the evolution and development of education. Furthermore, the paper discusses the ongoing education reforms in contemporary China, such as curriculum reform, teacher training, and the promotion of innovative education. It highlights the importance of improving educational resources, addressing the rigidity of the education system, and fostering a closer connection between education and employment. The paper concludes by emphasizing the need for comprehensive measures to overcome the bottlenecks in Chinese education, including increased investment, system reforms, and the cultivation of comprehensive talents with international vision and global competitiveness. Overall, this study provides valuable insights into the historical trajectory and future directions of Chinese education.